Characteristics of family community and emotional intelligence of children - Martowska, Katarzyna (Studia Psychologica: Theoria et praxis, 2007)
Starting point of the consideration is a thesis that formation of emotional intelligence depends strongly on functioning of the family. Unique relationship that occurs between parents and children is the best context for optimum development of all members of the family. The article presents results of own research that focused on searching a relation between perceptions of family interaction and emotional intelligence of children. In the research the Emotional Intelligence Questionnaire (INTE N. S. Schutte and co-authors, Polish adaptation by A. Jaworowska and A. Matczak) has been used as well as tools for examination of the family systems: Analyses of Family Environment, Family of Origin, M. Ryś and Analyses of Family Environment. Family of Own, M. Ryś. The results of the research showed that a relation between family environment and emotional intelligence of children exists. Children brought up in proper family distinguished themselves higher level of emotional intelligence then children brought up in improper families. Results of the research revealed also dependences between a level of emotional intelligence of parents and children.